The National Pharmaceutical Council: Endorsing the Construction of Imaginary Worlds in Health Technology Assessment - Paul C Langley (MDPI AG, 2020)
All too often, organizations embrace standards for health technology assessment that fail to meet those of normal science. A value assessment framework has been endorsed that is patently in the realm of pseudoscience. If a value assessment framework is to be accepted, then claims for the value of competing products must be credible, evaluable and replicable. If not, for example, when the assessment relies on the construction of an imaginary lifetime incremental cost-per-quality-adjusted-life-year (QALY) world, then that assessment should be rejected. Such an assessment would fail one of the central roles of normal science: the discovery of new facts through an ongoing process of conjecture and refutation where provisional claims can be continually challenged. It is no good defending an endorsement of a value framework that fails expected standards on the grounds that it has been endorsed by professional groups and reflects decades of development. This is intellectually lazy. If this is the case, then the scientific revolution of the 17th century need not have happened. The purpose of this commentary is to consider the recommended standards for health technology assessment of the National Pharmaceutical Council (NPC), with particular reference to proposed methodological standards in value assessment and the commitment to mathematically impossible QALYs.